Asksia AI LOGO

Sia

Question
Math
Posted 9 months ago

Match each function to its antiderivative, where t>3t>3 and CC is a constant.
\begin{tabular}{c|c} 
Antiderivative & Function \\
\hlineH(t)=ln(12t212)+CH(t)=\ln \left(12 t^{2}-12\right)+C & h(t)=3t23t33th(t)=\frac{3 t^{2}-3}{t^{3}-3 t} \\
H(t)=ln(t46t2)+CH(t)=\ln \left(t^{4}-6 t^{2}\right)+C & h(t)=4t212t36th(t)=\frac{4 t^{2}-12}{t^{3}-6 t} \\
H(t)=ln(4t312t)+CH(t)=\ln \left(4 t^{3}-12 t\right)+C & h(t)=2tt21h(t)=\frac{2 t}{t^{2}-1}
\end{tabular}
Sign in to unlock the answer
Answer from Sia
Posted 9 months ago
Solution by Steps
step 1
Identify the given functions and their potential antiderivatives from the table
step 2
For the function h(t)=3t23t33th(t) = \frac{3 t^{2} - 3}{t^{3} - 3 t}, simplify it to see if it matches any antiderivative: h(t)=3(t21)t(t23)=3tt21t23 h(t) = \frac{3(t^{2} - 1)}{t(t^{2} - 3)} = \frac{3}{t} \cdot \frac{t^{2} - 1}{t^{2} - 3} This does not simplify directly to a known form
step 3
For the function h(t)=4t212t36th(t) = \frac{4 t^{2} - 12}{t^{3} - 6 t}, simplify it: h(t)=4(t23)t(t26)=4tt23t26 h(t) = \frac{4(t^{2} - 3)}{t(t^{2} - 6)} = \frac{4}{t} \cdot \frac{t^{2} - 3}{t^{2} - 6} This also does not simplify directly to a known form
step 4
For the function h(t)=2tt21h(t) = \frac{2 t}{t^{2} - 1}, simplify it: h(t)=2t(t1)(t+1) h(t) = \frac{2 t}{(t - 1)(t + 1)} This matches the derivative of H(t)=ln(4t312t)+CH(t) = \ln(4 t^{3} - 12 t) + C because: ddtln(4t312t)=12t2124t312t=3t23t33t \frac{d}{dt} \ln(4 t^{3} - 12 t) = \frac{12 t^{2} - 12}{4 t^{3} - 12 t} = \frac{3 t^{2} - 3}{t^{3} - 3 t} Thus, H(t)=ln(4t312t)+CH(t) = \ln(4 t^{3} - 12 t) + C is the antiderivative of h(t)=2tt21h(t) = \frac{2 t}{t^{2} - 1}
step 5
Verify the remaining functions and antiderivatives: - H(t)=ln(12t212)+CH(t) = \ln(12 t^{2} - 12) + C matches h(t)=3t23t33th(t) = \frac{3 t^{2} - 3}{t^{3} - 3 t} - H(t)=ln(t46t2)+CH(t) = \ln(t^{4} - 6 t^{2}) + C matches h(t)=4t212t36th(t) = \frac{4 t^{2} - 12}{t^{3} - 6 t}
Answer
The correct matches are: - H(t)=ln(12t212)+CH(t) = \ln(12 t^{2} - 12) + C with h(t)=3t23t33th(t) = \frac{3 t^{2} - 3}{t^{3} - 3 t} - H(t)=ln(t46t2)+CH(t) = \ln(t^{4} - 6 t^{2}) + C with h(t)=4t212t36th(t) = \frac{4 t^{2} - 12}{t^{3} - 6 t} - H(t)=ln(4t312t)+CH(t) = \ln(4 t^{3} - 12 t) + C with h(t)=2tt21h(t) = \frac{2 t}{t^{2} - 1}
Key Concept
Matching functions to their antiderivatives
Explanation
To match a function to its antiderivative, simplify the function and compare it to the derivative of the given antiderivative.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question